Analýza výsledků perkutánních extrakcí konkrementů - Macek, P; Novák, K; Hanus, T; Babjuk, M; Pesl, M; Safarík, L; Fógel, K; Soukup, V; Dvorácek, J; Sedlácek, J; Stolz, J; Capoun, O (Casopis lekaru ceskych, 2007)
BACKGROUND: Percutaneous nephrolithotomy is an effective less invasive method for the treatment of nephrolithiasis. Authors retrospectively analysed results of this procedure performed in a single centre (Department of Urology, General University Hospital, Prague) from January 2005 till June 2007. METHODS AND RESULTS: Patients were acquired by an analysis of operating reports performed over a period January 2005 till June 2007 and subsequently a retrospective analysis of electronic and paper patient's records was carried out. Percutaneous nephrolithotomy was performed in 150 patients. Of those, 117 (78%) patients underwent primary and 33 (21.3%) secondary procedure. Analysed group consisted of 85 (56.7%) men and 65 (43.3%) women. Right-sided procedure was performed in 46% (69 times) and left-sided in 54% (81 times) of cases. Mean patient's age was 52.9 years (SD +/- 16.3). Mean stone size was 18.3 (SD +/- 9.5) mm. Staghorn calculi were present in 19 (12.7%) patients and 77 (51.3%) patients had more than 1 stone. Intracorporeal lithotripsy was necessary in 82 (54.7%) cases. Seventy eight (52.9%) patients were stone free after the procedure. There were 24 (16%) patients with an anatomic abnormality of upper urinary tract. The most common (in 64.3%) component in analysed stones was a calcium oxalate. CONCLUSIONS: The amount of stone free patients is rather lower compared to the literature results. However, definitive results are always affected by auxiliary procedures (mainly extracorporeal shock wave lithotripsy), which are not included in the analysis.
Keywords: Male; Child, Preschool; Adolescent; Child; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; perkutánní nefrostomie; mladiství; Urinary Calculi; předškolní dítě; močové kameny; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Nephrostomy, Percutaneous; Female; lidé středního věku; Middle Aged